Finasteride Quantification in Human Plasma by High-Performance Liquid Chromatography Coupled to Electrospray Ionization Tandem Mass Spectrometry. Application to a Comparative Pharmacokinetics Study - Moreno, R. A.; Moreno, P.; Borges Jr, N. C.; Donato, J. L.; Oliveira, S. E.; Borges, N. C. (Drug Research, 2015)
A specific, fast and sensitive LC-MS/MS assay was developed for the determination of finasteride in human plasma using betamethsone dipropionate as the internal standard (IS). The limit of quantification was 1.0 ng/ml and the method was linear in the range of 1.0–25.0 ng/ml. The retention times were 0.75 min for finasteride and 0.85 min for IS. Method intra-batch precision and accuracy ranged from 3.6 to 7.1%, and 96.6 to 103.9%, respectively. Inter-batch precision ranged from 2.5 to 3.4%, while Inter-batch accuracy ranged from 100.3 to 103.5%.The analytical method was applied to evaluate the pharmacokinetic and relative bioavailability of 2 different pharmaceutical formulations containing 1.0 mg of finasteride. This study evaluated 38 volunteers in a randomized, 2-period crossover study with 7 days washout period between doses. The geometric mean and respective 90% CI of finasteride test/reference percent ratios were 95.68% (91.2 – 104.6%) for Cmax, 97.5% (92.1 –103.3%) for AUC0-t and 98.1 (92.67−103.8) for AUC0-inf. Based on the 90% confidence interval of the individual ratios (test formulation/reference formulation) for Cmax and AUC0-inf, it was concluded that the test formulation is bioequivalent to the reference one with respect to the rate and extent of absorption of finasteride.
Keywords: clinical pharmacology; estrogen; bioequivalence